Change your business with NLP : powerful tools to improve your organisation's performance and get results - Agness, Lindsey (Chichester, west sussex, U.K. : Capstone, 2010)
"A step-by-step guide to using NLP tools & techniques in your business. Covers four areas of management in both big and small businesses: personal, team, organization and clients. It looks at common challenges and shows how NLP can contribute to problem solving, improving all aspects of the work environment, and even to turning failing businesses around. Introduction - Why is NLP important to business? Part One: Transforming Leaders with NLP Building Strategies for Success Developing a Mindset for Success Role Modelling for Success Part Two: Transforming Teams with NLP Constructing High Performing Teams Encouraging Creativity Having Courageous Conversations Part Three: Transforming Organizations with NLP Managing Change Changing the Rules of the Game Developing Global Organizations Part Four: Transforming Client Relationships with NLP Influencing with Integrity Exceeding expectations Are you Ready?"--
"A step-by-step guide to using NLP tools & techniques in your business. Covers four areas of management in both big and small businesses: personal, team, organization and clients. It looks at common challenges and shows how NLP can contribute to problem solving, improving all aspects of the work environment, and even to turning failing businesses around"--
Includes bibliographical references (p. [309]-310) index.
Keywords: Neurolinguistic programming; Leadership; Management; Organizational change